Apple powdery mildew caused by Podosphaera leucotricha: some important features of biology and epidemiology - Holb, I. J. (International Journal of Horticultural Science, 2009)
In this review, some important features of biology and epidemiology are summarised for apple powdery mildew (Podosphaera leucotricha). In the first part of the review, the geographical distribution or the pathogen are discussed, then the morphology and taxonomy of the causal organism are described. Disease symptoms or apple powdery mildew are also shown and then host susceptibility/resistance is discussed in relation to durability of resistance. In the second part of this review, the general disease cycle of powdery mildew on apple are demonstrated and some basic features of powdery mildew epidemiology (such response of the pathogen to temperature, relative humidity, and rain as well as spore production, spore dispersal, diurnal patterns and temporal dynamics of the pathogen/disease) are also given on apple host.